2014
DOI: 10.1099/mic.0.073437-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic characterization of Escherichia coli O157 : H7 based on IS629 distribution and Shiga toxin genotype

Abstract: Shiga toxin (stx)-producing Escherichia coli O157 : H7 is a prominent food-borne pathogen. Symptoms in human infections range from asymptomatic to haemorrhagic colitis and haemolytic uraemic syndrome, and there is a need for methods that yield information that can be used to better predict clinical and epidemiological outcomes. IS629 is an insertion sequence notable for its prevalence and variable distribution in the chromosome of E. coli O157 : H7, which has been exploited for subtyping and strain characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 57 publications
4
17
0
Order By: Relevance
“…These results show that the presence of IEE and IS629 appears to be related to a strain H-type (lineage specific) and that this IEE and IS629 combination appears to be associated mostly with serotypes related to high pathogenicity and human disease (SPT A and B). This supports other findings by Stanton et al, who found an association between the presence of IS629 and elements with an effect on virulence and phage production (32).…”
Section: Discussionsupporting
confidence: 82%
“…These results show that the presence of IEE and IS629 appears to be related to a strain H-type (lineage specific) and that this IEE and IS629 combination appears to be associated mostly with serotypes related to high pathogenicity and human disease (SPT A and B). This supports other findings by Stanton et al, who found an association between the presence of IS629 and elements with an effect on virulence and phage production (32).…”
Section: Discussionsupporting
confidence: 82%
“…These results supported recent epidemiological studies that demonstrated higher association between stx 2a and clinical outcome, as compared to stx 2c (Andersson et al, 2011;Beutin et al, 2007;Persson et al, 2007). In the present study, a strong correlation between stx 2a /stx 2c genotypes and LSPA-6 genotypes was observed, supporting a recent postulation that both lineage types, together with stx genotype, may be informative surrogate markers for epidemiological and evolutionary investigations (Stanton et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…To assess the public health risks associated with E. coli O157 : H7, it is crucial to understand the phenotypic and genotypic differences among strains from clinical illness, as well as from their sources of infection, that might enable better prediction of clinical and epidemiological outcomes (Stanton et al, 2014). Molecular typing and microbial genomics have facilitated the characterization and comparison of E. coli O157 : H7 strains recovered from different isolation sources demonstrating non-random distribution of genotypes among clinical and non-clinical strains (Besser et al, 2008;Franz et al, 2012;Hartzell et al, 2011;Lee et al, 2011;Whitworth et al, 2010;Yang et al, 2004;Yokoyama et al, 2011;Zhang et al, 2010;Ziebell et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenome Architecture and Virulence Profiles of Stx (−) NSF O157:H7 and SF O157:NM Alterations in genome size and architecture in EHEC O157:H7/NM are driven by the individual prophage complement, particularly Stx-phages Eppinger et al, 2011b;Shaaban et al, 2016) and dynamics of other MGEs (Eppinger et al, 2011b;Yokoyama et al, 2011;Stanton et al, 2014;Toro et al, 2015). We compared the chromosomes of the Stx (−) NSF O157:H7 and SF O157:NM strains with BRIG (Alikhan et al, 2011) using Stx (+) strain EC4115 (stx1−, stx2a+, stx2c+) as reference (Eppinger et al, 2011b).…”
Section: Resultsmentioning
confidence: 99%